Description of a Dialectical Behavior Therapy program in a Veterans Affairs Health Care System. (June 2022) - Phalen, Peter; Grossmann, Jessica; Bruder, Tiffany; Jeong, Jae Yeon; Calmes, Christine; McGrath, Kathleen; Malouf, Elizabeth; James, Alison; Romero, Erin; Bennett, Melanie
Abstract: A comprehensive Dialectical Behavior Therapy (DBT) program was created within a VA Health Care System for patients with recent psychiatric hospitalization, suicidality and/or significant emotion dysregulation. The program was notable for being one of a relatively small number of comprehensive DBT programs in the VA system, and for including patients with psychosis and psychotic disorder, with a majority of patients (58%) having a documented history of psychosis or endorsing psychotic symptoms in assessments. We describe the process of creating this program at a VA medical center and present preliminary program evaluation data. All patients completed assessments of suicidality (C-SSRS), emotion dysregulation (DERS), skills use and dysfunctional coping (DBT-WCCL), borderline symptomatology (BSL-23), and depression (PHQ-9) at program entry and subsequently every 6–8 weeks through program completion. Suicide attempts and hospitalizations were also tracked. Twelve patients completed multiple (up to six) assessment timepoints, allowing for evaluation of change during treatment. Patients demonstrated improvements on most measures and no hospitalizations or suicide attempts during active treatment, and the subsample with psychosis showed average improvements on every outcome measure. Eleven of 12 patients completed a full six-month rotation.